Effect of social app-assisted education and support on glucose control in patients with coronary heart disease and diabetes mellitus - Zhong, Jing; Zhang, Huimin; Li, Zhuyu; Qian, Dehui; Zhang, Yingqian; Li, Chao; Song, Yuanbin; Qin, Zhexue; Yu, Jie; Bian, Shi-zhu; Yu, Yang; Wang, Ke; et al. (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Social app assisted education and support may facilitate diabetes self-management. We aim to evaluate the effect of WeChat, a popular social app, on glycemic control in patients with coronary heart disease (CHD) and diabetes mellitus (DM). METHODS: We conducted a parallel-group, open-label, randomized clinical trial that included 160 patients with both CHD and diabetes mellitus from a tertiary hospital in China. The intervention group (n=80) received educational materials (information on glucose monitoring, drug usage, medication, and lifestyle) and reminders in response to individually blood glucose values via WeChat. The control group (n=80) received usual care. The primary outcome was change in glycated hemoglobin (HbA1C) levels over 3 months. Secondary outcomes included fasting blood glucose, systolic blood pressure and low-density lipoprotein (LDL) cholesterol from baseline to 3 months. Analysis was conducted using linear mixed model. RESULTS: The intervention group had a greater reduction in HbA1C (-0.85% versus 0.15%, between-group difference: -1.00%; 95% CI, −1.31% to −0.69%; P<0.001) compared with the control group. Change in fasting blood glucose was larger in the intervention group (−1.53 mmol/L; 95% CI, −1.90 to −1.17; P<0.001) and systolic blood pressure (−9.06 mmHg; 95% CI, −12.38 to −5.73; P<0.001), but not LDL (between-group difference, -0.08 mmol/L; 95% CI, -0.22 to 0.05; P=0.227). CONCLUSIONS: The combination of social app with education and support resulted in better glycemic control in patients with CHD and DM. These results suggest that education and support interaction via social app may benefit self-management in CHD and DM.